Utilizing the theory of planned behavior to Prediction the safety driving behaviors in truck drivers in Bandar Abbas 1392 - Masoud Ashoogh; Teymur Aghamolaei; Amin Ghanbarnejad; Abdolhamid Tajvar (Iranian Association of Health Education and Health Promotion, 2013)
Introduction: Road accident is one of the main leading causes of mortality and disability in the world. The purpose of this study was to predict the driving behaviors of truck drivers based on the theory of planned behavior (TPB) in Bandar Abbas. Methods: This cross-sectional study was conducted on 240 truck drivers in Bandar Abbas terminal in June 2013. The data were collected by a questionnaire including demographic characteristics and a questionnaire based on the TPB constructs. Multiple regression and correlation analyses were used to predict safety driving behaviors base on theory of planning behavior Results: The mean age of drivers was 38.3 (SD=9.8) years and the mean experience of driving was 13.8 (SD=9). Multiple regression analyses revealed that attitude and perceived behavioral control could predict the intention for safe driving behavior (R2=0.21, F=14, p<0/001). Drivers who had more positive attitude and more perceive behavior control were more likely to have intention toward driving safety. Furthermore, behavioral intention and perceive behavioral control predicted safety driving behaviors (R2=0. 14, F=27, p<0.001). The drivers who had more intention and more perceived behavioral control were more likely to drive safety. Conclusion: Based on the results, the attitude and perceived behavioral control predicted the safety behavior therefor it is suggested to design programs for improving attitude and perceived behavioral control of truck drivers